Efecto de la administración de sulfato ferroso dos veces por semana para la reducción de la anemia en niños de 6 a 35 meses de edad, durante 6 meses y durante 12 meses de suplementación en comunidades rurales de Ancash, Perú - Morán Tello y Cols., Andrés (2019)
Iron-deficiency anemia is highly prevalent in Peru. It mainly affects children under 3 years. In the past 10 years the prevalence has declined slightly and remains high especially in the population living in the mountains and rural areas. Caritas Peru in the Ancash region developed between 2007 and 2011 Micuy Ally Project, with support from the Antamina Mining Fund, which was achieved significant reduction in chronic malnutrition and anemia in children. Our objective is to show the efficacy of twice weekly administration of ferrous sulfate supplements for reducing anemia in children 6 to 35 months of age in rural communities in Ancash, Peru. This is a retrospective observational research. The project was determined Ally Micuy initial hemoglobin level of children 6 to 35 months, using HemoCue photometer. According to the levels of hemoglobin, ferrous sulfate was administered 1 to 2 mg of elemental iron per kilo of body weight per time, twice a week as a preventive dose and 3 to 5 mg of elemental iron per kilo of body weight once twice a week as a therapeutic dose. Ferrous sulfate supplementation was provided by the Community Educational Nutrition. Hemoglobin was analyzed at 6 and 12 months. We observed that the percentage of children aged 6 to 35 months with anemia decreased from 62.58% to 45.71% after one semester of supplementation (n = 4001). After the second consecutive semester of supplementation, the percentage of anemia decreased from 68.28% to 31.57% (n = 2623). The average concentration of hemoglobin was 10.29gr/dl, and 11.23gr/dl 10.78gr/dl at baseline, at 6 and 12 months of supplementation, respectively. Therefore, we conclude that supplementation made by the Nutrition Community Educational team twice a week is effective in reducing anemia in children 6 to 35 months of age. The decrease in the prevalence of anemia in children by administration of ferrous sulfate is much greater when the children are supervised supplementation during two consecutive semesters.